Exploring the Context of Canadian Graduate Student Teaching Certificates in University Teaching - Kenny, Natasha; Watson, Gavan P.L.; Watton, Claire (Canadian Journal of Higher Education, 2014)
A growing number of Canadian universities offer graduate student certificate programs in university teaching. This paper examines such programs at 13 Canadian universities and presents a discussion of program structures and practices. The findings suggest that most programs were offered over one to two years, and upon successful completion, participants were issued a centre-approved certificate paired with a more formalized method of recognition, such as a transcript notation. The core focus of certificate programs appears to be divided between those that emphasize practical skill development (46%) and those that offer practical skill development along with a focus on the scholarship of teaching and learning (54%). Most certificates included active and authentic assessment methods, such as dossiers (69%), and practice teaching sessions (62%). These findings help to inform the continued evolution of graduate student teaching certificate programs.